Assessment of antenatal care quality in Ethiopia: Facility-based study using service provision assessment data. - Addisu Alehegn Alemu; Alec Welsh; Theodros Getachew; Marjan Khajehei (PLoS ONE)
Background Antenatal care (ANC) coverage in low- and middle-income countries has increased in the past few decades. However, merely increasing care coverage may not enhance maternal and newborn health unless the recommended service components are also provided. Our aim was to assess the quality of ANC and its associated factors in Ethiopia. Methods We used data from 2,042 pregnant women whose first ANC consultation was observed. Data were obtained from the 2021-2022 Ethiopian Service Provision Assessment survey conducted among a nationally representative sample of 1,158 healthcare facilities. Twenty-four components of ANC were assessed, and their values were summed to generate a total ANC quality score (range: 0-24). A higher score indicated a superior ANC quality. A multiple generalized Poisson regression model was fitted to identify factors influencing the quality of ANC. All statistical analyses were performed using STATA version 16. Results The mean ANC quality score was 11 (standard deviation [SD]: 3.8). Blood pressure measurement was the most commonly performed ANC component, at 79.5%, and breast examination for cancer screening was the most neglected component of ANC, at 3.3%. ANC quality was higher in the Amhara region (incidence rate ratio [IRR]: 1.088; 95% confidence interval [CI]: 1.0-1.171) and Southern Nations, Nationalities, and Peoples' Region (IRR: 1.081; 95% CI: 1.002-1.166), and when the care was provided by a female healthcare worker (IRR: 1.054; 95% CI: 1.021-1.088). On the other hand, ANC quality decreased in rural healthcare facilities (IRR: 0.964; 95% CI: 0.932-0.998), clinics (IRR: 0.666; 95% CI: 0.581-0.764), and health posts (IRR: 0.817; 95% CI: 0.732-0.91). Similarly, ANC quality decreased when gestational age at the first antenatal visit increased (IRR: 0.994; 95% CI: 0.992-0.996) and when care was received from a non-nearby healthcare facility (IRR: 0.956; 95% CI: 0.923-0.990). Conclusion Overall, the quality of ANC in Ethiopia is suboptimal. Encouraging women to initiate ANC early and utilize nearby facilities, assisting providers in delivering standardized services through preservice training, supervision, and continuous education, and ensuring the availability and proper use of necessary resources at all facilities are important to improve ANC quality.